2018
DOI: 10.15666/aeer/1602_18351853
|View full text |Cite
|
Sign up to set email alerts
|

Plant Traits and Biomass Allocation of Gentiana Hexaphylla on Different Slope Aspects at the Eastern Margin of Qinghai-Tibet Plateau

Abstract: Abstract. The growth, biomass partitioning and reproduction of alpine Gentiana hexaphylla species in local microclimates have important ecological significance in the study of the adaptation strategies of alpine plants. At the eastern edge of the Qinghai-Tibet Plateau in China we set up eight sample positions surrounded by mountains at an altitude of 4000 m and subsequently transplanted and measured the indices of growth, biomass allocation and reproduction of Gentiana hexaphylla to investigate the adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Consequently, enhancing reproductive fitness prioritizes vegetative fitness in X. strumarium along elevation. Besides MYT, AYH, DLH, and altitude, additional environmental variables like soil OM %, N %, EC, TDS, N, and E may be significant in PFT's plasticity and are described by authors such as Cheng et al ( 2015 ), Mason et al ( 2017 ), and Xue et al ( 2018 ). In addition, genetic differentiation, gene flow, and phenotypic plasticity may provide plants with an adaptive ability to dealing with climatic change along altitude gradients (Gonzalo‐Turpin & Hazard, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, enhancing reproductive fitness prioritizes vegetative fitness in X. strumarium along elevation. Besides MYT, AYH, DLH, and altitude, additional environmental variables like soil OM %, N %, EC, TDS, N, and E may be significant in PFT's plasticity and are described by authors such as Cheng et al ( 2015 ), Mason et al ( 2017 ), and Xue et al ( 2018 ). In addition, genetic differentiation, gene flow, and phenotypic plasticity may provide plants with an adaptive ability to dealing with climatic change along altitude gradients (Gonzalo‐Turpin & Hazard, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that when elevation increases, S. marianum ’s reproductive ability takes priority over its vegetative ability. Moreover, soil OM and N%, EC, N, and longitude may also have a role in PFT plasticity; this has been shown by researchers such as Mason et al (2017) ; Xue et al (2018) , and Chen et al (2020).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, we considered these closely related species, often co-occurring with G. hexaphylla , to collectively be part of the G. hexaphylla complex in this study. The G. hexaphylla complex occurs widely across the HM ( Ho and Pringle, 1995 ; Ho and Liu, 2001 ), tends to reproduce sexually via outcrossing in open sunny habitats ( Xue et al, 2018 ), and some species have horticultural value. Despite this interest, taxonomic confusion remains problematic for this group of species.…”
Section: Methodsmentioning
confidence: 99%